IMPLEMENTASI KEBIJAKAN KARTU IDENTITAS ANAK (KIA) DI KABUPATEN LEBAK - Julizar Idris; Anti Annisa Subhiyati; Ondy Asep Saputra; Arif Nugroho; Jumanah Jumanah (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2024)
The Central Government's efforts to implement the Child Identity Card (KIA) program as the newest population administration program, namely to become a concrete form of protection for children as the state's obligation to protect every citizen, where recently there has been a phenomenon of deprivation of civil rights for children. This research aims to determine the implementation of the Child Identity Card (KIA) policy or program at the Lebak Regency Population and Civil Registration Service. This implementation can be known by using the concept of Policy Implementation according to George C. Edward III whose dimensions include Communication, Resources, Disposition, Bureaucratic Structure. The research was conducted using descriptive methods with a qualitative approach. The results of the research show that the implementation of the Child Identity Card (KIA) program in Lebak Regency has not been fully maximized, one of which can be seen from the socialization which has not been maximized, then the delivery of information which is not clear, the condition of the facilities is less than optimal, the attitude and commitment of the Dukcapil Office in implementing the KIA program Less than optimal and assessment of the implementation of the KIA program that is less than optimal. Recommendations for this research; (1) Socialization should go directly to the school, involving teachers and student guardians. (2) Provide clear information both offline and online. (3) The condition of the seating facilities must be improved. The recommendation for further research is to conduct a policy evaluation study to assess the output of the KIA program in Lebak Regency in particular and generally to carry out comparative studies in several regions in Indonesia.